Pengaruh Kualitas Pelayanan Dan Citra Perusahaan Terhadap Kepuasan Konsumen TB PADA MAJU Kota Bandung - Sri Ayu Rachmawati; Saad Noor (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This analysis intends to obtain results from, 1. Dominance of Service Quality with regard to Customer Satisfaction, 2. Dominance of Service Quality with regard to Company Image, 3. Dominance of Service Quality and Company Image with regard to Customer Satisfaction. The form of analysis used is descriptive analysis (explanatory research) through a quantitative strategy. The model used is 12 models as employees of TB PADA MAJU and several consumer respondents who shop in a day. The process of collecting the model used is accidental sampling, the data collection n technique uses a respondent's questionnaire. By using descriptive analysis. Keywords : Service Quality, Customer Satisfaction, Company Image